Signifikansi Argumentasi Kesejarahan Dalam Memahami Sabda Nabi SAW - Sugito, Mohamad Shofin (The International Journal of Pegon : Islam Nusantara civilization, 2024)
The article analyses the significancy of historical argumentation in interpreting The Prophet’s sayings. The research uses library research within qualitative-descriptive approach. The study demonstrates the paradigm of integration between Islam and historical science. Islam here means the Prophets’s sayings as a great text belonging to the past, but having biggest influence to the present. So, it is about great outhority and impact, either literally or interpretively. Thus, the text and its horizon of situation become an interesting study of historical science. By examining the integration, the article pays the particular attention to Ali Mustafa Yaqub, Ulama, Lecture on hadith studies, and great Imam of Istiqlal Mosque. Finally, The article argues that the Prophet’s sayings are a sacral artifact relating to holy man in the past, and the historical argumentation is an important approach working to understand and interprate the Prophet’s teachings, either its about worship, morality and social relationship. Artikel ini menganalisis signifikansi argumentasi sejarah dalam menafsirkan sabda Nabi. Penelitian ini menggunakan penelitian kepustakaan dengan pendekatan deskriptif kualitatif. Kajian tersebut menunjukkan paradigma integrasi antara Islam dan ilmu sejarah. Islam yang dimaksud di sini adalah sabda Nabi sebagai kitab besar milik masa lalu, namun mempunyai pengaruh paling besar hingga saat ini. Jadi, ini tentang kekejaman dan dampak yang besar, baik secara harfiah maupun interpretasi. Dengan demikian, teks dan cakrawala situasinya menjadi kajian ilmu sejarah yang menarik. Dengan mengkaji integrasi tersebut, artikel ini memberikan perhatian khusus kepada Ali Mustafa Yaqub, Ulama, Pengajar kajian hadis, dan Imam Besar Masjid Istiqlal. Terakhir, artikel tersebut berargumen bahwa sabda Nabi merupakan artefak suci yang berkaitan dengan orang suci di masa lalu, dan argumentasi sejarah merupakan pendekatan penting yang berupaya memahami dan menafsirkan ajaran Nabi, baik tentang ibadah, moralitas, dan hubungan sosial.